2020
DOI: 10.1177/1359104520969765
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation difficulties and psychopathology among Pakistani adolescents

Abstract: The main aim of this study was to examine the associations between emotion dysregulation and psychopathology in adolescence. A representative sample of 1,500 adolescent students (50% female) aged 12 to 19 years ( M = 15.08, SD = 1.44) was recruited from schools and colleges located in the province of district Punjab, Pakistan, using a stratified sampling technique. Structural equation modeling (SEM) was used to test associations between five dimensions of emotion regulation difficulties and five forms of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…Although emotion regulation is a universal process, it is highly sensitive to cultural differences ( Ford & Mauss, 2015 ). Some studies on emotion regulation have been conducted with Pakistani Muslim samples ( Jabeen et al, 2013 ; Zafar et al, 2021 ); however, these have focused on parenting practices as predictors of emotion regulation or have linked emotion regulation with psychopathological tendencies. Another study from the same cultural context has analyzed cognitive reappraisal as a mediator linking executive cognitive functioning with Machiavellian adjustment ( Fatima & Shahid, 2020 ).…”
Section: Religious Coping Cognitive Emotion Regulation and Mental Wel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although emotion regulation is a universal process, it is highly sensitive to cultural differences ( Ford & Mauss, 2015 ). Some studies on emotion regulation have been conducted with Pakistani Muslim samples ( Jabeen et al, 2013 ; Zafar et al, 2021 ); however, these have focused on parenting practices as predictors of emotion regulation or have linked emotion regulation with psychopathological tendencies. Another study from the same cultural context has analyzed cognitive reappraisal as a mediator linking executive cognitive functioning with Machiavellian adjustment ( Fatima & Shahid, 2020 ).…”
Section: Religious Coping Cognitive Emotion Regulation and Mental Wel...mentioning
confidence: 99%
“…Empirical evidence from the same cultural context has shown gender differences in emotion regulation difficulties and its association with psychopathology. Specifically, adolescent girls compared with boys scored lower on limited access to effective emotion regulation and this variable positively predicted psychopathology in girls only ( Zafar et al, 2021 ). Moreover, Fatima and Shahid (2020) found that mediated links between cognitive functioning, cognitive reappraisal, and Machiavellian adjustment were stronger for women compared with men.…”
Section: Current Study In the Covid Context In Pakistani Culturementioning
confidence: 99%
“…When a person lacks the skills or fails to execute the skills appropriately, emotions become less effective, and instead of motivating adaptive behaviour, it may lead to maladaptive behaviours, including HRBs. Findings indicate that among the adult sample, deficits in emotion regulation may induce distress, dysregulation of which further drive individuals to engage in HRBs such as drug abuse, alcohol abuse, sexual risk behaviours, bullying, aggressive behaviours, unhealthy dietary behaviours, addictive behaviours, unintentional injuries or violence-related behaviours, suicidal behaviours, and lack of medical adherence (Garofalo & Velotti, 2017 ; Lansing et al, 2019 ; Ram et al, 2018 ; Weiss et al, 2015 ; Zafar et al, 2021 ).…”
Section: Emotion Regulation and Hrbsmentioning
confidence: 99%
“…Emotional reactivity is related to emotions’ sensitivity, continuity, and intensity (Nock et al, 2008 ). Emotions’ rapid changes and emotional regulation problems cause multiple maladaptation problems and psychopathologies (Millgram et al, 2020 ; Zafar et al, 2021 ). People with high emotional reactivity are at risk of experiencing emotionally negative situations more (Buehler & Welsh, 2009 ; Maremmani et al, 2018 ).…”
Section: Forgiveness Happiness and Emotional Reactivitymentioning
confidence: 99%